Stepped care and digital intervention service model design in the multidisciplinary sleep service - Sara Winter; Sara Crocker; Tricia Rolls; Deanne Curtin; Jessica Haratsis; Irene Szollosi (Internet Interventions)
In order to ensure access to insomnia treatment in our public health environment of increasing patient acuity, increasing demand and health care costs, we need to innovate and implement systematised models of care to achieve better outcomes and efficiencies.The design of a new Stepped Care treatment model in the multidisciplinary sleep disorders service with consumer and stakeholder engagement is described. Patients, their referrers and staff were surveyed to explore their views and preferences towards Stepped Care, including digital transformation. A consensus group workshop using the Nominal Group Technique was undertaken with the multidisciplinary team to develop the model of care.The team endorsed a hierarchy of treatment steps beginning with digital intervention, group and trainee interventions as first line, escalating to more intensive 1:1 ‘upstream’ for higher acuity presentations. Referrer surveys highlighted the need for education in primary care settings about the availability of evidence-based internet treatment options. While few patients were aware of the availability of digital insomnia intervention, they were largely supportive of digital transformation. Barriers and risks to the Stepped Care approach were identified which informed the refinement of the treatment pathway.Stepped Care treatment models offer adaptability and flexibility, allowing for adjustments in interventions based on patients' response to treatment, and preventing unnecessary escalation of care while reducing costs and improving efficiencies.